In search of the spin-out entrepreneur - Matteo Landoni; Dt Ogilvie (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
A spin-out happens when an employee quits a company to start a new venture; however, theories do not agree on whether the "spin-out entrepreneur" will start the company in the same or in a different industry. We investigated a sample of 250 entrepreneurs and 120 spin-out companies to understand what led an entrepreneur or a group of founders to enter a new industry. Our results contribute to theory, suggesting that spin-out entrepreneurs usually move to different and innovative industries owing to recombination of knowledge in founding teams. Our evidence supports the positive effect of different experiences within the team.
Keywords: 650; entrepreneurial behaviour; entrepreneurship; founder; industry experience; knowledge flow; organisational limitations; spin-out